2015
DOI: 10.1186/s12916-015-0459-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of statin therapy on coronary plaque composition: a systematic review and meta-analysis of virtual histology intravascular ultrasound studies

Abstract: BackgroundVirtual histology intravascular ultrasound (VH-IVUS) imaging is an innovative tool for the morphological evaluation of coronary atherosclerosis. Evidence for the effects of statin therapy on VH-IVUS parameters have been inconclusive. Consequently, we performed a systematic review and meta-analysis to investigate the impact of statin therapy on plaque volume and its composition using VH-IVUS.MethodsThe search included PubMed, Cochrane Library, Scopus and Embase (through 30 November 2014) to identify p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
120
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 187 publications
(130 citation statements)
references
References 48 publications
6
120
0
4
Order By: Relevance
“…Simvastatin would also inhibit the biosynthesis of isoprenoid intermediates such as geranyl and farnesyl pyrophosphate, and then affect the posttranslational prenylation of several important cellsignaling proteins during immune responses [11]. Therefore, simvastatin has been shown to have antitumor potential in many different cell lines [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin would also inhibit the biosynthesis of isoprenoid intermediates such as geranyl and farnesyl pyrophosphate, and then affect the posttranslational prenylation of several important cellsignaling proteins during immune responses [11]. Therefore, simvastatin has been shown to have antitumor potential in many different cell lines [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in further build up and thickening of atherosclerotic plaques, as well as effects on external elastic membranes and fibrous and dense calcium volumes is achieved by statin therapy (Banach et al 2015). Dual antiplatelet therapies using cyclooxygenase inhibitors such as aspirin and P2Y12 inhibitor such as clopidogrel are first-line treatments for prevention of CVDs, which aim to reduce clot formation and platelet aggregation (Kapil et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Besides their lipid-lowering effects, statins exhibit pleiotropic properties such as anti-inflammatory [10] , antioxidant [11] , antihypertrophic and antifibrotic effects, which might play a role in CV protection [12] . Statins can slow the progression or even induce regression of atherosclerosis [13] , which may reduce myocardial ischemia, which can cause ventricular arrhythmias, and in consequence reduce the risk of SCD [14] . Large scale clinical trials indicated that statins reduce CV morbidity and mortality in high-risk populations [15] .…”
Section: Introductionmentioning
confidence: 99%